Overview of clinical pharmacology in cancer 1 - Kolesar, Jill (Henry Stewart Talks, 2017)
Principles of pharmacokinetics, Key influences on pharmacokinetic parameters (adsorption, distribution, metabolism and elimination), Role of pharmacokinetic studies in drug development